PENGARUH SUBSTITUSI TEPUNG SUKUN TERHADAP KUALITAS ROTI MANIS - Novitasari, Herlina; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
The background of this study was the lack of utilization materials local food namely sukun flour. The purpose of this research was to analyzed substitution effect of sukun flour peel as much as 20%, 30% and 40% to the quality of volume, skin color, shape, aroma, texture and taste of sweet breads. This type of research was purely experimental with a completely randomized design method. The data used were primary data sourced from 5 expert panelists namely culinary lecturers by proposed the organoleptic test format. Analyzed of data using ANAVA, if Fcount> Ftable then continued with Duncan test. The result of the research showed that there was a significant influence of sukun flour substitution on sweet bread quality as much as 20% produced the best quality,covering volume exspands, aroma sukun, fine texture.Keywords: Sukun, sweet bread, Quality of sweet bread